Evaluation of Green Solvents’ Applicability for Chromatic Reintegration of Polychrome Artworks - Andrea Macchia; Camilla Zaratti; Chiara Biribicchi; Irene Angela Colasanti; Francesca Irene Barbaccia; Gabriele Favero (Heritage, 2023)
Organic solvents are commonly used in restoration treatments, including chromatic reintegration on polychrome artworks. They are often toxic, and their vapors have a high impact on the environment and restorers, possibly causing pathological conditions. Therefore, this study aims at defining a new green solvent that can be used for chromatic reintegration, maintaining the volatility and the desired physical–chemical properties. The dispersion forces value (Fd) of ethyl lactate was taken as reference for a comparison with the proposed solvents, since it was found to be the most used solvent for the dilution of Maimeri Restoration Colors (MRC) and Gamblin Conservation Colors (GCC). Based on the Teas fractional parameters, six solutions based on acetals and ethanol have been proposed and tested. They were mixed with both MRC and GCC, and applied on prepared canvases. The difference between the backgrounds made with reference solvent and the one made with the proposed alternatives was evaluated through spectrocolorimetric measurements. Fourier-transform infrared spectroscopy in the attenuated total reflectance mode (FTIR-ATR) was performed on the applied layers to evaluate the presence of residual solvent inside them, while the volatility of the solvents was assessed by performing gravimetric analysis. The study showed that acetals, acetals’ blends, and acetals–ethanol mixtures represent suitable alternatives for the dilution of Gamblin Conservation Color and Maimeri Restoration Colors.